CODE MIXING OF SIPITUHUTA LANGUAGE IN MEREK WEDDING CEREMONY - Br Nainggolan, Mirawati; Meisuri, Meisuri (Universitas Negeri Medan, 2019)
The research is aimed at discussing code mixing in Merek wedding ceremony. The theories in this thesis is about code mixing. The method used in this thesis is descriptive qualitative design. The objectives of this research are to find out the types of code mixing used by the speakers of Merek wedding ceremony and describe the function of the reasons why the speakers using code mixing on Merek wedding ceremony and also to explain why the speakers using code mixing on the utterances. The result of the research applied Muysken(2000) showed there are 3 types of code mixing consisted in the utterances on the wedding namely : Insertion, Alternation, Congruent lexicalization, then the function of code mixing supported by Hoffman (1991) namely : Talking about particular topic , Being emphatic about something, Quoting somebody else, and Intention of clarifiying the speech content interculator from the 17 utterances. The findings are expacted to contribute a better understanding of code mixing.